Preliminary Evaluation of Dekoko Field Pea (Pisum sativum var. abyssinicum) Accessions at Kulumsa and Dehera, South Eastern Ethiopia - Abo, Temesgen; Yimam, Kedir; Tesfaye, Deressa (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during July to September, 2021 at Kulumsa and Dhera, Ethiopia to study the genetic variability among yield and yield related traits of abyssinian field pea. Thirteen accessions of field pea (Pisum sativum var. abyssinicum) along with one standard and one local check from the species Pisum sativum were evaluated at two locations in a randomized complete block design with three replications. Combined analysis of variance revealed highly significant (p<0.01) for locations. Grain yield performances of the accessions were ranged from low of 1539 kg ha-1 to high yield of 4520 kg ha-1 followed by 3728 kg ha-1 for standard check Megeri, respectively. The estimated values for phenotypic coefficient of variation (PCV) are higher than their counter genotypic coefficient of variation (GCV) values. A heritability as high as 98% were recorded for days to flowering and days to maturity. Cluster analysis grouped into three distinct classes with number of genotypes in each cluster ranged from two to nine. Principal component (PCs) analysis revealed the first two PC were contributed for 70.7% of the entire phenotypic variation observed among the 15 field pea genotypes. Generally, the use of multivariate analysis including principal component and cluster analysis, and coefficient of variance analysis were effectively used to estimate the level of existing genetic variability in field pea genotypes under study. The result indicated that there is a potential for genetic improvement through selection in this field pea species.